Pemanfaatan Jamu Herbal (Sehat Nifas) Dan Air Rebusan (Pinang Muda, Daun Sirih Dan Asam Kandis) Terhadap Percepatan Pemulihan Masa Nifas Early Puerperium - Arriza, Nurul; Windiyati, Windiyati; Melyani, Melyani; Handayani, Luluk; BE, Gloria Fortunata; Liza, Erviana; Evi, Evi (Biota, 2023)
Postnatal herbal medicine and boiled water are herbs are usually given to postpartum mothers to strengthen the body and speed up the recovery period of the uterus, speed up the cessation blood and healing perineal wounds. Method: Quasi Experimental research type Pretest-Posttest Nonequivalent Control Group Design. Held at PMB Nuripah Kubu Raya on 21-27 November 2023. Total sample was 34 respondents, the respondents were divided randomly into 2 groups, postpartum mothers in intervention group were given 1x1 multivitamin and postnatal healthy herbal medicine test ingredients at a dose of 1x1 suchet (25 grams) and Postpartum mothers in control group were given 1x1 multivitamin as a comparison, the research was carried out for 7 days. Results: The intervention group had an effect on changes in uterine involution based on anteroposterior diameter (p. 0.005), changes in uterine involution based on longitudinal length (p. 0.002), the amount of locheal discharge (p. 0.003), the smell of locheal discharge (p. 0.002), reducing the pain scale (p. 0.000) and perineal wound healing (0.003). Conclusion: Healthy postpartum herbal medicine and perineal wound fluid effective accelerating early puerperium period (uterine involution, lochea and perineal wounds) with the fastest start of action compared to the control group (multivitamin).